Implementation Interactive Media and Characterized Meme Media: A Comparation Study - Sumarsono, Adi; Sianturi, Murni (Journal of Education and Vocational Research, 2018)
This study aimed to determine the effectiveness of the implementation of interactive media and characterized meme media on the student learning. This study applied experimental research method which used simple random sampling technique. The participants of the study consisted of two group as group A amount twenty-nine students and group B amount twenty-eight students. Each group had a different treatment, for the group a was treated by implementing interactive media, while group B was treated by implementing characterized memes media. Data analysis applied hypothesis testing of paired sample t-test and obtained that both of implementing of interactive media, and implementing characterized memes media, probability value .00 was less than alpha value, .05, which means the media provide impact to the student learning. Data analysis applied hypothesis testing of independent sample t-test and obtained p, .972 was greater than alpha value, .05. Thus, there was no difference between student learning achievement taught by using interactive media and characterized memes media. However, in accordance with effective criteria, it was presented that interactive learning media is more effective than characterized memes media. The percentage of classical completeness of students who were taught by using interactive learning media enhanced to 89.12 percent, while using characterize memes learning media reach 60.41 that not reached the classical completeness. In addition, in terms of appropriate student learning activity in the classroom using interactive media reached 90.12 percent, while in memes characterized media class character merely 66.65 percent.